Direct‐Space Structure Determination of Covalent Organic Frameworks from 3D Electron Diffraction Data. Issue 50 (6th October 2020) - Sun, Tu; Hughes, Colan E.; Guo, Linshuo; Wei, Lei; Harris, Kenneth D. M.; Zhang, Yue‐Biao; Ma, Yanhang
Abstract: Structure determination of covalent organic frameworks (COFs) with atomic precision is a bottleneck that hinders the development of COF chemistry. Although three‐dimensional electron diffraction (3D‐ED) data has been used to solve structures of sub‐micrometer‐sized COFs, successful structure solution is not guaranteed as the data resolution is usually low. We demonstrate that the direct‐space strategy for structure solution, implemented using a genetic algorithm (GA), is a successful approach for structure determination of COF‐300 from 3D‐ED data. Structural models with different geometric constraints were considered in the GA calculations, with successful structure solution achieved from room‐temperature 3D‐ED data with a resolution as low as ca. 3.78 Å. The generality of this strategy was further verified for different phases of COF‐300. This study demonstrates a viable strategy for structure solution of COF materials from 3D‐ED data of limited resolution, which may facilitate the discovery of new COF materials in the future. Abstract : The direct‐space strategy for structure solution, implemented using a genetic algorithm (GA), is shown to be a successful approach for structure determination of COF‐300 from low‐resolution 3D electron diffraction data.